A Comparative Study of SIMULINK 1D Dynamic Model and FLUENT 3D Model for PEMFC Faults Diagnosis - Pei, Fenglai; Wang, Nan; Zhou, Su (International Journal of Online and Biomedical Engineering (iJOE), 2013)
According to the different research platforms of PEMFC (Proton Exchange Membrane Fuel Cell) faults diagnosis, experimental diagnostics and mathematical modeling are employed in the characterization and determination of fuel cell performance. The methods based on mathematical modeling are promised on establishing a suitable model, which is capable to reflect the physical properties of actual fuel cell stack as accurate as possible. Further, a scientific and reasonable PEMFC model is also indispensable for the system performance analysis, design, control, and optimization. Generally, PEMFC auxiliary system adopts a lumped parameter model to provide the boundary conditions of stack, such as current demand, gas flow rate, pressure, and temperature. As PEMFC stack needs to be embedded particular faults in a specific time and space position, it necessitates adopting a distributed parameter model in one dimensional (1D), two dimensional (2D) or three dimensional (3D). In this paper, a comparative analysis is carried out between a diagnostic one dimensional dynamic model by MATLAB/SIMULINK and a diagnostic three dimensional distributed parameter model based on FLUENT. Also, the diagnostic results in specific faults are studied.